Exploring the influence of leadership styles on psychological well-being and satisfaction of Pilates classes clients - Youngmi Kim; Soowon Chae; Insuk Sim; Buom Kim (BMC, 2024)
Abstract Background The recent trend of increased indoor activities has significantly influenced daily life, enhancing the popularity of exercises like Pilates. This study explores how Pilates instructors' leadership styles affect class satisfaction and psychological well-being, addressing the research gap concerning the specific impact of leadership within the context of Pilates classes. Methods The study surveyed 388 participants from 39 Pilates studios across South Korea, utilizing a questionnaire to assess leadership styles (transformational, transactional, and servant leadership), class satisfaction, and psychological well-being. Using statistical analyses, leadership styles were assessed for their correlation with class satisfaction and psychological well-being. Results Findings revealed that transformational and transactional leadership styles were positively correlated with class satisfaction and psychological well-being. Specifically, transformational leadership significantly enhanced educational satisfaction and personal growth, while transactional leadership most strongly influenced social satisfaction and the sense of purpose in life. Servant leadership was notably effective in improving physical class satisfaction. The study also highlighted the critical role of class satisfaction in promoting psychological well-being among participants. Conclusion This research underscores the importance of leadership styles in enhancing the Pilates class experience, suggesting that instructors' leadership approaches can significantly impact participants' satisfaction and psychological well-being. The study advocates developing training programs that equip Pilates instructors with the skills to adopt effective leadership styles, fostering a more positive and fulfilling class environment.